Anodic substitution reaction of carbamates in a flow microreactor using a stable emulsion solution. Issue 11 (11th October 2021) - Mikami, Rio; Nakamura, Yuto; Shida, Naoki; Atobe, Mahito
Abstract : An anodic substitution reaction in a flow microreactor using a stable emulsion solution prepared by tandem acoustic emulsification is demonstrated. Abstract : An anodic substitution reaction in a flow microreactor using a stable emulsion solution prepared by tandem acoustic emulsification is demonstrated for the first time. The emulsion solution facilitated the selective anodic oxidation of carbamates, and the α-substituted products were ejected from the flow reactor to suppress overoxidation, resulting in an increase in the current efficiency for the desired reaction.